Parallel Molecular Evolution of Catalases and Superoxide Dismutases—Focus on Thermophilic Fungal Genomes - Katarína Chovanová; Miroslav Böhmer; Andrej Poljovka; Jaroslav Budiš; Jana Harichová; Tomáš Szemeš; Marcel Zámocký (Antioxidants, 2020)
Catalases (CAT) and superoxide dismutases (SOD) represent two main groups of enzymatic antioxidants that are present in almost all aerobic organisms and even in certain anaerobes. They are closely interconnected in the catabolism of reactive oxygen species because one product of SOD reaction (hydrogen peroxide) is the main substrate of CAT reaction finally leading to harmless products (i.e., molecular oxygen and water). It is therefore interesting to compare the molecular evolution of corresponding gene families. We have used a phylogenomic approach to elucidate the evolutionary relationships among these two main enzymatic antioxidants with a focus on the genomes of thermophilic fungi. Distinct gene families coding for CuZnSODs, FeMnSODs, and heme catalases are very abundant in thermophilic Ascomycota. Here, the presented results demonstrate that whereas superoxide dismutase genes remained rather constant during long-term evolution, the total count of heme catalase genes was reduced in thermophilic fungi in comparison with their mesophilic counterparts. We demonstrate here, for the newly discovered ascomycetous genes coding for thermophilic superoxide dismutases and catalases (originating from our sequencing project), the expression patterns of corresponding mRNA transcripts and further analyze translated protein sequences. Our results provide important implications for the physiology of reactive oxygen species metabolism in eukaryotic cells at elevated temperatures.